Investigation of Anti-inflammatory, Antioxidative, and Cardioprotective Effects of Combined Metformin and Exercise in Rats - Şerif Demir; Halit Diril; Murat Tekbaş; Ali Gök; Özge Beyazçiçek; Ersin Beyazçiçek (Düzce Tıp Fakültesi Dergisi)
Aim: This study aimed to investigate the anti-inflammatory, antioxidative and cardioprotective effects of exercise and metformin treatment applied alone or in combination.Material and Methods: In this study, 42 male Wistar rats were used. The rats were separated into six groups as control (CONT), exercise (EXE), 100 mg/kg metformin (M100), 200 mg/kg metformin (M200), 100 mg/kg metformin+exercise (M100+EXE), and 200 mg/kg metformin+exercise (M200+EXE). Exercise was applied for 10 weeks including exercise training. Metformin was administered 30 minutes before exercise. At the end of the study, levels of C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-10 (IL-10), cardiac troponin-I (cTn-I), creatine kinase-muscle/brain (CK-MB), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and malondialdehyde (MDA) in serum samples from rats were quantified using the ELISA method.Results: The combined application of metformin and exercise significantly decreased cTn-I, CK-MB, MDA, TNF-α, CRP and IL-6 levels (p